Diseño y construccion a nivel piloto de un sistema de almacenamiento para pitaya - Forero, J.A.=700 1 Medina, J.R.; Garcia, M.C.; Garcia, H.R.
(En, Es)
Ilus., 27 ref.
Keywords: ALMACENAMIENTO; TECNOLOGIA POSTCOSECHA; DEPOSITOS DE ALMACENAMIENTO; VENTILACION; REDUCCION; TEMPERATURA; FRUTAS; COLOMBIA; SELENICEREUS MEGALANTHUS; PITAHAYA; HUMIDIFICACION; CORPOICA